From the Archives of the Zagreb Antirabies Clinic: Hospitalized Persons due to Animal Bites from 2007 to 2021 (Part Two) - Radovan Vodopija; Dora Primorac; Jelena Boneta; Kruno Sokol; Daniela Vojvodić (Acta Clinica Croatica)
The aim of this paper is to present data on hospitalized patients in Zagreb clinics and hospitals, from 2007 to 2021. This paper is a continuation of our previous paper, but for a different time period. All data were collected from the official patient registry of the Zagreb Antirabies Clinic, which operates within the Reference Center for Rabies at Andrija Štampar Teaching Institute of Public Health. During this period, there were 9960 patients examined for injuries inflicted by animals, of which 98 (0.98%) were hospitalized in different departments and hospitals in Zagreb due to wound severity. All the hospitalized patients were examined to exclude the possible risk of rabies. The official patient registry of the Zagreb Antirabies Clinic is the source of the presented data, which were collected and analyzed retrospectively. We conducted a descriptive analysis. The ages of the hospitalized patients ranged from 17 days to 82 years, 55 (56.12%) were adults, and 43 (43.88%) were children; among the adults, there were 29 (29.59%) men and 26 (26.53%) women, while among the children there were 25 (25.51%) boys and 18 (18.37%) girls. The most common causes of hospitalization after an animal bite were infectious diseases (cat-scratch disease, rat-bite fever) and severity of wounds, which is comparable to the data available from other countries. There is no statistically significant difference in the frequency of hospitalization between children and adults, while dogs are statistically significantly more likely to inflict injuries that result in hospitalization than other animals. However, no specific anatomical location exhibited a statistically significant higher frequency of bites compared to others, as one might expect.